How Does a TPACK-related Program Support EFL Pre-service Teachers’ Flipped Classrooms? - Kusuma, I Putu Indra (LEARN Journal: Language Education and Acquisition Research Network, 2022)
A worldwide discussion about Technological Pedagogical Content Knowledge (henceforth, TPACK)-related program or a program that provides technology, pedagogy, and content courses related to EFL flipped classrooms is scarce. Thus, the present study aimed at exploring (1) how a TPACK-related program supported the EFL pre-service teachers’ understanding of flipped classrooms and their implementation, and (2) how a TPACK-related program supported the pre-service English teachers’ technology integration in their flipped classrooms. This study employed a basic qualitative approach and recruited three EFL pre-service teachers who implemented flipped classrooms as participants. The data were collected by administering semi-structured interviews using an interview guide. Other documents were also collected to ensure the trustworthiness of the data. Then, the data were analyzed using the data analysis spiral strategy. The results revealed that the TPACK-related program helped the EFL pre-service teachers improve their understanding of flipped classrooms, develop considerations when implementing flipped classrooms, and successfully implement technology in their flipped classrooms. This study also provides three implications for improving the TPACK-related program worldwide, especially when teaching content about flipped classrooms approach.